Impact of Air Temprature and Humidity on Sick Building Syndrome among Bank Employees - Arifin; Zubaidah, Tien; Ratodi, Muhamad (Gema Lingkungan Kesehatan, 2025)
Sick Building Syndrome (SBS) is a condition in which inhabitants develop health problems or discomfort as a result of extended exposure to indoor surroundings. The purpose of this study was to investigate the association between air temperature and humidity in air-conditioned rooms and the prevalence of SBS, specifically mental weariness (burnout) instances, among employees of Bank Syariah Indonesia (BSI) in Banjarbaru City, Indonesia. The study followed a quantitative design with an analytical cross-sectional survey approach. Data were gathered using questionnaires and devices that measured air temperature and humidity. Univariate analysis defined the variable features, whereas bivariate analysis looked at the correlations between air temperature and humidity (independent variables) and the prevalence of SBS mental fatigue cases (dependent variable). The survey included 30 bank employees, with an average age of 32.4 years. The average air temperature was 25.8°C, with a relative humidity of 84.2%, which was outside of the permissible limit. The prevalence of SBS was 43.3%, with common symptoms including nose discomfort, eye irritation, headache, and fatigue. The prevalence of mental weariness was 36.7%. Pearson correlation analyses found significant positive relationships between air temperature and SBS prevalence (r = 0.48, p < 0.01), relative humidity and SBS prevalence (r = 0.39, p < 0.05), air temperature and mental fatigue (r = 0.41, p < 0.05), and relative humidity and mental fatigue. The findings emphasize the need of maintaining adequate indoor environmental conditions to reduce SBS risk and increase employee well-being in air-conditioned workplaces.